Optimizing the density of Stark decelerated radicals at low final velocities: a tutorial review - Dominik Haas; Sebastian Scherb; Dongdong Zhang; Stefan Willitsch (EPJ Techniques and Instrumentation, 2017)
Abstract The Stark deceleration technique can produce molecular beams with very low velocities. In order to maximize the density of decelerated molecules, experimental parameters such as the velocity, the velocity spread and the spatial spread of the initial molecular beam as well as the operation characteristics of the decelerator have to be chosen appropriately. In this tutorial review, we describe procedures for the optimization of the density of Stark decelerated radicals for low-velocity applications which are of interest in, e.g., molecule trapping and cold-collision studies.